UTILIZATION OF FERMENTED ORGANIC WASTES OF TOFU, RICE BRAN, AND CHICKEN MANURE TO INCREASE THE CULTURE PRODUCTION AND QUALITY OF SILK WORM (Tubifex sp) - Diana Chilmawati; Suminto .; Tristiana Yuniarti (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2015)
The Effect of enrichment culture media through the combination of fermented tofu waste, rice  bran,  chicken  manure  to  increase  the  production  and  quality  of  silk  worm, Tubifex sp.  was studied  in  this  research.    The  experiment  method  was  employed  in  this  research  by  using complitely  randomized  design  pattern  with  four  treatments  and  three  replicates,  respectively. Those  treatments  were  the  combinations  of  0%  tofu  waste,  0%  rice  bran,  and  100%  chicken manure (A), 35% tofu waste, 15% rice bran, and 50% chicken manure (B), 25% tofu waste, 25% rice  bran,  and  50%  chicken  manure  (C),  and  15%  tofu  waste,  35%  rice  bran,  and  50%  chicken manure as  D  treatment.    The  results  shown  that  the  enrichment  culture  media  through  the combination of tofu waste, rice bran, and chicken manure were siqnificantly effect (p<.05) on the total biomass production and protein content, but no siqnificantly effect on the total length growth of  silk  worm, Tubifex sp. However, the combination of 35% tofu  waste, 15 rice bran,  and 50% chicken manure was the best production and quality of silk worm, Tubifex sp.Key word : Tubifex sp., agriculture organic wastes, fermentation, quality, and culture production